IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DALAM PEMBELAJARAN MEMBACA AKSARA BALI DI KELAS XI SMA DHARMA PRAJA DENPASAR - Sugiarti, Ni Kadek Mira (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2024)
This research explores the application of the Think Pair Share (TPS) Cooperative Learning Model in learning to read Balinese script at SMA Dharma Praja Denpasar. The TPS model is designed to increase interaction between students, which can be seen from students' active participation and enjoyment when discussing with their friends. This research focuses on three main aspects: (1) Implementation of the TPS model by teachers in learning to read Balinese script; (2) Obstacles faced by students in understanding Balinese script and the teacher's efforts to overcome them; (3) Results from the application of the TPS model in improving Balinese script reading skills in class XI IPS 1. Data was collected through observation and analyzed qualitatively using behavioristic and constructivist theories. Research findings show that the use of the TPS model can facilitate students in understanding Balinese script, although there are still obstacles in understanding the rules of Balinese script literature. To overcome these obstacles, the efforts made included intensive learning regarding the rules and forms of Balinese script and script hangings. This research emphasizes the importance of understanding Balinese script as a vital means of preserving Balinese culture.